2013
DOI: 10.1016/j.vaccine.2013.05.070
|View full text |Cite
|
Sign up to set email alerts
|

MF59-adjuvanted and virosomal influenza vaccines for preventing influenza hospitalization in older people: Comparative effectiveness using the Valencia health care information system

Abstract: During the 2010-2011 influenza season, we found no differences in the risk of influenza hospitalization in subjects aged ≥65 years vaccinated with MF59-TIV compared with those vaccinated with virosomal-TIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…IVE was estimated using the widely used test-negative approach, which has been shown to give consistent results[15], and the analysis of IVE was restricted to periods with similar influenza circulation patterns[16], [35]. Furthermore, the IVE was calculated on the basis of ORs determined using a random effects model, which allowed us to take into account potential differences, including type of vaccine, vaccination programs, the levels of immunity across different population and settings, and different use of hospital emergency departments [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…IVE was estimated using the widely used test-negative approach, which has been shown to give consistent results[15], and the analysis of IVE was restricted to periods with similar influenza circulation patterns[16], [35]. Furthermore, the IVE was calculated on the basis of ORs determined using a random effects model, which allowed us to take into account potential differences, including type of vaccine, vaccination programs, the levels of immunity across different population and settings, and different use of hospital emergency departments [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Abucasis contains an ambulatory information system called SIA, which registers any medical contact (visit), and the attending physician uses a drop-down menu with the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) to record diagnoses. Abucasis also links other databases: Care Provision Management (GAIA), which is the drug information system available to the different professionals involved in prescription and dispensation, addressed from the Department of Health; and the Vaccine Information System (RVN) [40]. Other databases used in this study, such as the Hospital Data Surveillance System (CMBD), are described elsewhere [41] and can be linked through a unique personal identification number (SIP), for the collection of demographic data.…”
Section: Methodsmentioning
confidence: 99%
“…The MF59 oil-in-water adjuvant (Adj) emulsion enhances influenza responses in the elderly and is licensed for immunization of individuals aged 65 years and older (9)(10)(11). In infants, a first trial evaluating MF59-adjuvanted versus nonadjuvanted monovalent A/H1N1 influenza vaccines between 6 and 36 months of age showed that MF59-adjuvanted formulations generated higher response rates with persistent seroprotection (12).…”
mentioning
confidence: 99%